Interactions Between Drought and Plant Genotype Change Epidemiological Traits of Cauliflower mosaic virus - Bergès, Sandy E.; Vile, Denis; Vazquez-Rovere, Cecilia; Blanc, Stéphane; Yvon, Michel; Bédiée, Alexis; Rolland, Gaëlle; Dauzat, Myriam; van Munster, Manuella (Frontiers in Plant Science, 2018)
Plants suffer from a broad range of abiotic and biotic stresses that do not occur in isolation but often simultaneously. Productivity of natural and agricultural systems is frequently constrained by water limitation, and the frequency and duration of drought periods will likely increase due to global climate change. In addition, phytoviruses represent highly prevalent biotic threat in wild and cultivated plant species. Several hints support a modification of epidemiological parameters of plant viruses in response to environmental changes but a clear quantification of plant-virus interactions under abiotic stresses is still lacking. Here we report the effects of a water deficit on epidemiological parameters of Cauliflower mosaic virus (CaMV), a non-circulative virus transmitted by aphid vectors, in nine natural accessions of Arabidopsis thaliana with known contrasted responses to water deficit. Plant growth-related traits and virus epidemiological parameters were evaluated in PHENOPSIS, an automated high throughput phenotyping platform. Water deficit had contrasted effects on CaMV transmission rate and viral load among A. thaliana accessions. Under well-watered conditions, transmission rate tended to increase with viral load and with CaMV virulence across accessions. Under water deficit, transmission rate and virulence were negatively correlated. Changes in the rate of transmission under water deficit were not related to changes in viral load. Our results support the idea that optimal virulence of a given virus, as hypothesized under the transmission-virulence trade-off, is highly dependent on the environment and growth traits of the host.